Brake Thermal Efficiency dan Exhaust Gas Temperature Mesin Bensin Berbahan Bakar Gasoline-Butanol - Sanjaya, Firman Lukman; Fatkhurrozak, Faqih; Syarifudin; Nur Akhmadi, Amin (P3M Politeknik Negeri Cilacap, 2024)
The development of butanol as a gasoline additive is encouraged by the government to reduce pollution and the fuel crisis. This is because butanol is a green fuel that is environmentally friendly and can be produced. In addition, the octane number and high oxygen concentration in butanol optimize engine performance and improve exhaust emissions. This research correlates engine power and Brake specific fuel consumption (BSFC) with the BTE of gasoline-butanol-fueled engines and identifies the content of Nox compounds in exhaust gases through engine Exhaust Gas Temperature (EGT). The percentage of butanol in gasoline is 5% -15%. Engine speed from 1000-3000 rpm. Dynotest is used to measure BTE while the thermocouple is used to measure exhaust gas temperature. This research proves that the addition of butanol increases energy absorption which is converted into power with effective fuel consumption which means BTE increases. The highest BTE increase was 21.7% in the B15 blend. EGT decreased by 8.6% in the B16 mixture compared to B0. This identifies that the concentration of Nox in the exhaust gas also decreases.